MOOC: Improve the Quality of MOOCs - Teixeira, António (2020)
The poster presents the MOOQ´s vision, mission and main goal. MOOQ's vision: to foster quality in MOOCs leading to anew era of learning experiences.The MOOQ’s mission: to develop a quality reference framework (QRF) for the adoption, the design, the delivery and the evaluation of MOOCs in order to empower MOOC providers for the benefit of the learners. The MOOQ's main goal: the development and the integration of quality approaches, new pedagogies and organisational mechanisms into MOOCs with a strong focus on the learning processes, methodologies and assessments.